Flow of electrorheological fluid under conditions of slip on the boundary - R. H. W. Hoppe; M. Y. Kuzmin; W. G. Litvinov; V. G. Zvyagin (Abstract and Applied Analysis)
We study a mathematical model describing flows of electrorheological fluids. A theorem of existence of a weak solution is proved. For this purpose the approximating-topological method is used.